2012
DOI: 10.1111/joor.12014
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between gagging severity and its management in dentistry

Abstract: The purpose of this study was to investigate how grading according to our new gagging reflex index correlated with patient background and subsequent management. After obtaining institutional approval and informed consent, 110 patients with a gagging problem were enrolled. The patients completed the State-Trait Anxiety Inventory (STAI), the Dental Anxiety Scale (DAS), and a health questionnaire at initial consultation. On the second visit, an intra-oral examination was carried out and the severity of gag reflex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 21 publications
4
50
0
1
Order By: Relevance
“…Other research that has focused exclusively on patients with problem gagging found a high degree of dental fear in such patients as a whole, but not differentiated across gagging severity levels. 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other research that has focused exclusively on patients with problem gagging found a high degree of dental fear in such patients as a whole, but not differentiated across gagging severity levels. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Reviews and recent empirical studies have been published on the myriad techniques available to manage gagging problems in dentistry. 1,7,29 Future work should address which of these techniques are most effective for reducing problems with gagging and whether certain methods are most appropriate for different severities of gagging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the benefits include adjunctive pain control (13)(14)(15), behavior management (16), reduction of the gag reflex (17), and the reduction of fear and anxiety (2,7,9,11). The use of minimal and moderate sedation in endodontic practice allows for patient cooperation during treatment such as holding a radiographic sensor or film holder, opening or closing their mouth, and changing their head position (10,18).…”
mentioning
confidence: 99%
“…Although the GAS is positively correlated with patient anxiety levels [10], it does not assess the severity of a gag reflex during dental procedures. The 5-level Classification of Gagging Problem (CGP) assesses the severity of a patient's gagging reflex and classifies patients into those who can successfully be treated for desensitization of the gag reflex within one year and those who cannot [11]. Patients who scored a 1 or 2 (normal but not desensitized gagging or mild gagging) were desensitized within a year of treatment.…”
Section: Predictive Gagging Survey Gagging Severity Indexmentioning
confidence: 99%